Chemical Constituents of Aristolochia giberti - Marchesini, Alessandra M. [UNESP]; Prado, Giovana G. [UNESP]; Messiano, Gisele B. [UNESP]; Machado, Marcos B. [UNESP]; Lopes, Lucia Maria Xavier [UNESP] (Soc Brasileira Quimica, 2009)
Fourteen compounds were isolated from Aristolochia giberti. These included a new triterperne, (-)-onocera-8,8'-diol. In addition, 3-hydroxypropanoate, acetate, and formate were detected by NMR techniques, which suggests that they are derivatives from 2-butynedioate, which is not detected by (1)H NMR. GC-MS and chemometric analyses of essential oils from stems and leaves showed great similarity between this cultivated species in Brazil and that in Argentina, which allowed us to confirm the species identity and to differentiate the oils according to the plant parts.
Keywords: Aristolochia giberti; Aristolochiaceae; (-)-onocera-8,8 '-diol; essential oil; 2-butynedioate